The A.I. generated images in Indonesia's 2024 presidential election - Andreas James Darmawan; Samuel Rihi Hadi Utomo; Minhyuk Yoo; Lina Kurniawati Gea (Jurnal Desain, 2024)
National elections are the most important event in the democratic life of Indonesian. The 2024 national election will determine the future of the political and social path. Along with this, artificial intelligence (A.I.) technology has been able to create attractive images, this phenomenon has also entered the democratic party for the President and Vice President election of Indonesia in 2024. This research investigates the attractiveness of images, which are created by artificial intelligence (A.I.) to one of candidates for President and Vice President of Indonesia period 2024 - 2029. This research focuses on how branding practices work through political advertising by using artificial intelligence (A.I.) to create images that influence public perception and opinion; about candidates and political parties using visual and comparative analysis techniques. The method in this research uses descriptive qualitative; by analyzing literary sources, interviewing potential voters, and processing them within the scope of scientific studies of visual communication design. The research results show that images created by artificial intelligence (A.I.) have a strong visual appeal, thereby influencing potential voters in determining a particular candidate or political party. The research is expected to provide new insight into the role of visualization using artificial intelligence (A.I.) technology to attract sympathy politely and ethically, create a beautiful image, and influence the formation of public opinion in determining choices.